A model-based battery charging optimization framework for proper trade-offs between time and degradation - Appleton, Sean; Fotouhi, Abbas (Springer, 2023)
This study aims at developing an optimisation framework for electric vehicle charging by considering different trade-offs between battery degradation and charging time. For the first time, the application of practical limitations on charging and cooling power is considered along with more detailed health models. Lithium Iron Phosphate battery is used as a case-study to demonstrate the effectiveness of the proposed optimisation framework. A coupled electro-thermal equivalent circuit model is used along with two battery health models to mathematically obtain optimal charging current profiles by considering stress factors of state-of-charge, charging rate, temperature and time. The optimisation results demonstrate an improvement over the benchmark constant current-constant voltage (CCCV) charging protocol when considering both the charging time and battery health. A main difference between the optimal and the CCCV charging protocols is found to be an additional ability to apply constraints and adapt to initial conditions in the proposed optimal charging protocol. In a case study for example, the ‘optimal time’ charging is found to take 12 minutes while the ‘optimal health’ charging profile suggests around 100 minutes for charging the battery from 25% to 75% state-of-charge. Any other trade-off between those two extreme cases is achievable using the proposed charging protocol as well.
Keywords: Charging Optimisation; Battery Degradation; Electro-Thermal Equivalent Circuit Model; Electric Vehicles; Lithium Iron Phosphate